Arkitekturfotografier - Danmarks Kunstbibliotek (2016)
[Dt.:] Fotografische Sammlung dänischer Architektur der Dänischen Kunstbibliothek. - [Engl.:] The Library has a large collection of photographs of architecture in Denmark and abroad. In addition to this are special groups of photographs donated by individual architects, which cover everything from travel images to pictures of their own buildings. A special focus is Danish architecture during the period from the 1860s up to the end of the 1900 century. The Danish architectural photography collection are sorted by architect and / or topographically with a rather high accuracy, the foreign topographic at a slightly less dense level.